Diseño de un plan estratégico para la asociación de ganaderos de la sierra y oriente AGSO, institución gremial sin fines de lucro, que lidera la defensa de la producción lechera y del sector ganadero en general, ubicada en la ciudad de Quito - Rocha Cando, Liliana Elizabeth (2014)
This thesis aims to design a strategic plan for the breeders' association of the sierra and Eastern region. It is a Union institution nonprofit leading milk production in the livestock sector offering products and services to their members. The thesis consists of five chapters. In the first chapter the general characteristics of the research are developed to meet the purpose of the Association and research methodology. The second chapter is a study of the fundamental concepts that are used as a reference for the development of the strategic plan. The third chapter is the methodological process which determines the population and samples that are used for the development and design of the survey.